On Strong Deviation Theorems Concerning Arrays of Non-Negative Integer-Valued Random Variables (Journal of Mathematical Study, 2022)
In this article, by using the notion of general relative entropy as a measure of dependence of random variables, a kind of strong deviation theorems for the averages of array of integer-valued random variables are established. At the end of this paper, we give the upper and lower bounds for general moving averages of the form.